Antibacterial Activity of Two Metabolites Isolated From Endophytic Bacteria Bacillus velezensis Ea73 in Ageratina adenophora - Ren, Zhihua; Xie, Lei; Okyere, Samuel Kumi; Wen, Juan; Ran, Yinan; Nong, Xiang; Hu, Yanchun (Frontiers in Microbiology, 2022)
Ageratina adenophora, as an invasive and poisonous weed, seriously affects the ecological diversity and the development of animal husbandry. Weed management practitioners have reported that it is very difficult to control A. adenophora invasion. In recent years, many researchers focus on harnessing the endophytes of the plant as useful a resource for the development of pharmacological products for human and animal use. This study was performed to identify endophytes with antibacterial properties from Ageratina adenophora. Agar well diffusion method and 16S rRNA gene sequencing technique were used to screen and identify endophytes with antibacterial activity. The response surface methodology and prep –HPLC were used to determine the optimizing fermentation conditions and isolate secondary metabolites respectively. UV-visible Spectroscopy, Infrared Spectroscopy, Nuclear Magnetic Resonance and High Resolution Mass Spectrum were used to determine the structures of the isolated metabolites. From the experiment, we isolated a strain of Bacillus velezensis Ea73 (GenBank No. MZ540895) with broad-spectrum antibacterial activity. We also observed that the zone of inhibition of Bacillus velezensis Ea73 against Staphylococcus aureus was the largest when fermentation broth contained 6.55 g/L yeast extract, 6.61 g/L peptone, 20.00 g/L NaCl at broth conditions of 7.95 pH, 51.04 h harvest time and a temperature of 27.97 ℃. Two antibacterial peptides, Cyclo (L-Pro-L-Val) and Cyclo (L-Leu-L-Pro), were successfully extracted from B. velezensis Ea73. These two peptides exhibited mild inhibition against Staphylococcus aureus and Escherichia coli. Therefore, we isolated Bacillus velezensis Ea73 with antibacterial activity from A. adenophora. hence, its metabolites, Cyclo (L-Pro-L-Val) and Cyclo (L-Leu-L-Pro) could further be developed as a substitute for human and animal antibiotics.